Searching for identity; an investigation of Borgafjäll in the context of tourism development - Raunås, Felicia (My University, 2024)
As rural areas become developed and exploited as tourist destinations it occurs an imbalance between the visitors and the local population. The residents’ livelihood is dependent on that tourists will come and visit, therefore environments and experiences are created to please the expectations of the visitor. In a globalized world where both buildings and experiences become more similar to each other, it is important to cherish the local identity of each place, to include cultural heritage in all development and care for the residents and their traditions. The aim of the thesis is to explore a holistic approach to development of rural tourism in Sweden, with a specific focus on the rural mountain village of Borgafjäll in Västerbotten, Norrland. The past century Borgafjäll has evolved from families hosting guests in their homes to a thriving tourism destination, with future plans of further exploitation on the horizon. It is a place for several nature experiences, such as skiing, driving snowmobiles, hiking and fishing. There is a rich cultural heritage on the site, both from the Sami people, since the area is located in Sápmi, and the two characteristic buildings by Ralph Erskine. Guided by the philosophy of genius loci, the search for identity has however included morphology of all built environment and landscape, and the intangible layers in between. The thesis argues that the local inhabitants also need to be prioritized while developing a tourist resort with a majority of second homes, since they are the very core of the identity and genuine experience. Therefore the design proposal will act in favor for the permanent residents, through a Bygdegård (rural community center) while secondarily giving extra value for part-time visitors as well. The outcome of the thesis is both the findings made when searching for Borgafjäll’s identity - which is collected and curated in an archive, and the design intervention made within the frames of found identity. This is an iterative process where new findings inform the design throughout the project.
Keywords: rural development; tourism; cultural heritage; identity